Face2face : (Cambridge University Press, 2009)
Face2face is a six level general English course for adults and young adults. It goes from Starter level through to Advanced. The Student's Book provides approximately 80 hours of core teaching material, extendable to 120 hours using the photocopiable resources and extra ideas in the Teacher's Book. An interactive CD-ROM, packaged with the Student's Book, encourages learner autonomy with exercises in all language areas, video, games, customisable tests and a progress chart